JURIDICAL ANALYSIS OF THE IMPACT OF CATCALLING ON WOMEN AND SANCTIONS FOR CATCALLING ACTORS IN INDONESIA - Budi Hidayat; Yulia Hesti; Fauzi Fauzi (PRANATA HUKUM, 2021)
The large number of sexual harassments that occur in society is caused by theabsence of legal certainty that has been accepted by the perpetrators. One form of verbal sexual harassment is catcalling, most of the victims are women. Catcalling is carried out in public spaces such as public roads, public transportation, markets and even workplaces. The impact of catcalling is very bad because it will affect his psyche which can be seen from a psychological, emotional, anxious, fearful and uncomfortable feeling that can even lead to depression. Sanctions for Catcalling Actors in Indonesia are regulated in this Article, namely Article 281 Paragraph (2) of the Criminal Code, Article 8, Article 9, Article 34, Article 35 of the Law on Pornography. There are several basic reasons why the Pornography Law was used as a legal basis for catcalling, namely the definition of pornography as contained in Article 1 Number 1 General Provisions of Act of Number 44 Year 2008 concerning Pornography. The state is expected to be able to protect its citizens from catcalling by providing legal certainty, so that the perpetrators will no longer repeat or even commit the act. There are several basic reasons why the Pornography Law was used as a legal basis for catcalling, namely the definition of pornography as contained in Article 1 Number 1 General Provisions of Act of Number 44 Year 2008 concerning Pornography. The state is expected to be able to protect its citizens from catcalling by providing legal certainty, so that the perpetrators will no longer repeat or even commit the act.